Barriers to environmental management in clusters of small businesses in Brazil and Japan: from a lack of knowledge to a decline in traditional knowledge - Chiappetta Jabbour, Charbel Jose [UNESP]; Puppim-de-Oliveira, Jose Antonio (Taylor & Francis Inc, 2012)
This study aimed to examine the main barriers to environmental management (EM) in two clusters of small businesses (SBs). A study of two clusters was performed: one cluster in Brazil (the leather/shoe sector) and one cluster in Japan (traditional Japanese products). The case studies involved 23 interviews and an analysis of 12 SBs within these clusters. The Japanese cluster has more proactive environmental governance than the Brazilian cluster. The main barrier to environmental improvement in the Brazilian cluster is the lack of information; the main barrier to em in the Japanese cluster is the decline of traditional and environmentally friendly knowledge. The originality of the research is linked to the scarcity of studies of em within clusters and SBs, the comparative approach of the Brazilian and Japanese cases and the discovery of a new barrier to em for SBs (i.e. the decline of traditional knowledge).
Keywords: environmental management (EM); small businesses (SBs); clusters; Brazil; Japan